Development and Validation of Ecofriendly HPLC-MS Method for Quantitative Assay of Amoxicillin, Dicloxacillin, and Their Official Impurity in Pure and Dosage Forms. (17th June 2021) - Almalki, Atiah H.; Hussein, Essraa A.; Naguib, Ibrahim A.; Abdelaleem, Eglal A.; Zaazaa, Hala E.; Abdallah, Fatma F.
Abstract : Novel, accurate, selective, and rapid high-performance liquid chromatography mass spectrometry method was developed for simultaneous analysis of amoxicillin trihydrate, dicloxacillin sodium, and their official impurity 6-aminopenicillanic acid. The chromatographic separation was carried out by applying the mixture on a C18 column (3.5  µ m ps, 100 mm × 4.6 mm id) using acetonitrile:water (65 : 35 by volume) as a mobile phase within only 4 min. The quantitative analysis was executed using single quadrupole mass spectrometer in which electrospray ionization, selected ion monitoring, and negative mode were operated. The retention times were 1.61, 2.54, and 3.50 mins for amoxicillin, 6-aminopenicillanic acid, and dicloxacillin, respectively. The method was validated in linear ranges of 2–28  µ g mL −1, 2–35  µ g mL −1, and 1–10  µ g mL −1 for amoxicillin, dicloxacillin, and 6-aminopenicillanic acid, respectively. The results obtained from the suggested HPLC/MS were statistically compared with those obtained from the reported HPLC method, where no significant difference appeared respecting accuracy and precision. According to the analytical eco-scale assessment method, the proposed method was proved to be greener than the reported one, where the analysis time and the amount of the wasted effluent decreased.